The Insecticide Toxicity and Repelling Ability of Jeruk Purut (Citrus hystrix D.C) Leaf Extract on Maize Weevil (Sitophilus zeamais Motsch) - Wulansari, Alfia; Rochman, Nur; Setyono, Setyono (JURNAL AGRONIDA, 2019)
Sitophilus zeamais Motsch. is a primary storage insect pest damaging maize grains.Control of S. zeamais can be done by applying biopesticide. This study was aimed at assessing theability of Jeruk Purut leaf extract, as biopesticide, to kill and repel Sitophilus zeamais Motsch. Thestudy was conducted at Entomology Laboratory, Seameo Biotrop in March to August 2018. Acompletely randomized design with three replicates in each rate of Jeruk Purut leaf extract wasused. In preliminary pesticide toxicity experiment, five rates of Jeruk Purut leaf extract, namely0%, 2%, 4%, 6%, and 8% were applied. In preliminary repelling ability experiment, five rates ofJeruk Purut leaf extract, namely 1%, 2%, 4%, 6%, and 8% were applied. In the main pesticidetoxicity and repelling ability trial, five rates of Jeruk Purut leaf extract, namely 3%, 6%, 9%, 12%,and 15% were applied. Results showed that in 24 hour after treating (HAT) no significant effectswere found. Significant effects of Jeruk Purut leaf extract as insecticide on S. zeamais were foundin 48 and 72 HAT. The highest mortality rate (82.2%) of S. zeamais was found in 15% rate of JerukPurut leaf extract in 72 HAT. The application of Jeruk Purut leaf extract was not found to givesignificant effects on repelling S. zeamais in 24, 48, and 72 HAT as indicated in their sharplyfluctuating repellent values. The highest repelling ability (95%) was found in the application of9% Jeruk Purut leaf extract in 24 HAT. It was concluded that Jeruk Purut leaf extract was morepotential as insecticide repellent for Sitophilus zeamais Motsch.Key words: biopesticide, repellent, insecticide, maize, primary storage insect pest